2004
DOI: 10.1162/154247604323067989
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Financial Structure: Are Innovative Firms Different?

Abstract: We use data on publicly traded U.K. firms to investigate whether financing choices differ systematically with R&D intensity. As well as looking at a balance sheet measure of the debt/assets ratio, we also consider the probability of raising finance by issuing new equity, and the shares of bank debt and secured debt in total debt. We find a nonlinear relationship with the debt/assets ratio: firms that report positive but low R&D use more debt finance than firms that report no R&D, but the use of debt finance fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
127
2
23

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(164 citation statements)
references
References 12 publications
12
127
2
23
Order By: Relevance
“…On the contrary, for closely-held firms or firms in countries where the entrepreneur suffers strongly from stigmatization costs due to failure, in combination with human-capital intensive projects, we predict equity financing at both development stages. Both financing sequences are in line with Dang [2008] and Aghion et al [2004] who show that better growth opportunities and higher R&D investments are more probable to be financed via equity. Though, our model goes one step beyond the existing empirical evidence underlining the strong interaction which exists between the financing decision taken at the start-up stage and the subsequent financing as well as investment decisions.…”
Section: Introductionsupporting
confidence: 79%
“…On the contrary, for closely-held firms or firms in countries where the entrepreneur suffers strongly from stigmatization costs due to failure, in combination with human-capital intensive projects, we predict equity financing at both development stages. Both financing sequences are in line with Dang [2008] and Aghion et al [2004] who show that better growth opportunities and higher R&D investments are more probable to be financed via equity. Though, our model goes one step beyond the existing empirical evidence underlining the strong interaction which exists between the financing decision taken at the start-up stage and the subsequent financing as well as investment decisions.…”
Section: Introductionsupporting
confidence: 79%
“…We follow the influential approach developed by Rajan and Zingales (1998) Prior work on financing investments at the firm level also motivates our study (Aghion, et al 2004;Hall, 2002;Hall and Lerner, 2010). This research has demonstrated that firms first tap internal funds in order to maintain control rights over their innovations.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors support the positive impact of size on debt decisions (Warner, 1977;Ang et al, 1982;Dubois, 1985;Titman & Wessels, 1988;Rajan & Zingales, 1995;Bédué & Levy 1997;Booth et al, 2001;Voulgaris et al, 2004;Aghion et al, 2004;Huang & Song, 2006;Sheikh & Wang, 2011;Mateev et al, 2013). The existence of economies of scale associated with the diversification of the activities of large enterprises, reduces the volatility of their results (Fama & French, 2002).…”
Section: H6: There Is a Positive Relationship Between Commercial Debtmentioning
confidence: 98%